Dampak Penggunaan Keuangan Digital Dan Akses Keuangan Terhadap Pertumbuhan Umkm - Jihan Talasa; echan adam; Agustinus Moonti (Jurnal Pendidikan Indonesia, 2025)
The purpose of this research is to find out the use of digital finance and financial access to the growth of MSMEs, the method used in this study is a quantitative method using primary data, distributing questionnaires and then interviewing MSME actors who use digital finance This type of research is explanatory research research which intends to explain the position of the variables being studied and determine the influence of one variable with one variable others by using SEM (Strucural Equation Modeling) PLS (Partial Least Squares) data analysis. This research was conducted in the district of Gorontalo City with a total of 50 respondents who use digital finance. The results of this study show that the use of digital finance affects the growth of MSMEs with sufficient financial access.this shows that the use of digital finance with sufficient financial access can increase the growth of MSMEs in Gorontalo Province.